Eksplorasi Etnomatematika Pada Peninggalan Sejarah Dan Budaya Sumenep - Alvianto, Achmad Luthfi; Setianingsih, Rini (Universitas Negeri Surabaya, 2024)
In a culture that is spread across various societies, mathematical concepts are applied in it. The mathematical concept contained in this folk culture is called ethnomathematics. This study aims to find and describe mathematical concepts spread in the historical and cultural heritage of the Sumenep district community. This research is a qualitative descriptive study using an ethnographic approach. The research data were obtained from related literature, observations, interviews, documentation, and field notes. The informants in this study were a historian, a tourism ambassador, a royal family, three market traders, a Tong-tong activist, a traditional dancer, a batik entrepreneur, and a keris craftsman. The results showed that in daily activities and the culture in the Sumenep district, mathematical concepts are used by the people of Sumenep district. The Sumenep people use geometric concepts, namely straight lines, curved lines, parallels, triangles, squares, rhombuses, trapezoids, circles, cubes, beams, prisms, pyramids, cones, balls, and tubes in building designs and traditional games. The community also uses the concept of geometric transformation, namely congruence, translation, dilation, rotation, and reflection on the batik motifs they make. Also found the concept of set and comparison; these concepts are used in traditional Sumenep dance. With the study of mathematics in this culture, mathematics learning becomes more varied and contextual so that students will more easily understand abstract mathematical concepts.